Theatre in the 21st century, perspectives and reception of the scenic event. Introduction (XXI Century. Spanish Literature and Culture, 2024)
This text serves as a general introduction to our monograph entitled “Theatre in the 21st century, perspectives and reception of the stage event.” It presents the different articles that compose it, all of them of great richness and made by voices knowledgeable about theater and with great scientific foundation.
Keywords: contemporary Spanish theater; Spanish playwrights; theater and performance; theatrical theories